DOPUSZCZALNOŚĆ SKARGI KASACYJNEJ ZE WZGLĘDU NA PRZEDMIOT ZASKARŻENIA - Kincbok, Agnieszka (Zeszyty Prawnicze, 2017)
Admissibility of Cassation Complaint Subject to the Matter of Appeal Summary The cassation complaint is an appeal from sentences or decisions of courts of the second instance. After more than 40 years the cassation was reintroduced to the Polish civil proceedings by the amendment to the Civil Proceedings Code (CPC) of 1 March 1996. The court which handles cassation complaints is the Supreme C ourt located in Warsaw. The Supreme Court does not consider cases but examines whether the judicial decisions comply with applicable laws. The cassation complaint cannot be filed in all cases. The jurisdiction of the Supreme Court is limited by the type of the case and by the amount of the claim. This article addresses the question of when the cassation complaint is admissible (in civil proceedings, non - litigious proceedings, execution and bankruptcy proceedings and procedure for recognition and enforcement of foreign judgments) because of the criteria ratione materiae, i.e. subject, type of the case. The above-mentioned instrument is excluded, for example, in the cases examined in the simplified procedure, in alimony cases, some inheritance cases and from divorce sentences. This paper also discusses the ratione valoris criteria. According to the Rom an law rule de minimis non curat praetor, in cases concerning property rights cassation complaint is inadmissible when the am ount of the claim does not exceed the sum specified in the CPC.